Ipostases of The Choreographic Dialogue - Todi Cristina (Sciendo, 2019)
The analysis of the aesthetic face of dance brings to our forefront the fascination for the movement on many artists who experienced the movement and, above all, explored the possibilities of kinetic art or movement movement. In its most elevated form, dance contains not only this element but also the infinite richness of human personality. It is the perfect synthesis of the abstract and the human, of mind and intellect with emotion, discipline with spontaneity, spirituality with erotic attraction to which dance aspires; and in dance as a form of communication, it is the most vivid presentation of this fusion act that is the ideal show.